A importância do bibliotecário na educação infantil: Escola Rita Nery - SILVA, Tamires Mendes da (2017)
The following paper presents a study on the children's library, discusses the role of the library in the life of its users gathering information on how it should work a library aimed at this audience. What your services and activities should be and how a toy library can be used. It has the objective of demonstrating the results of the lack of a trained professional working in the place, since it is often replaced by another professional, teachers and pedagogues, for example. The research methodology used is a qualitative and descriptive field research. Held in the library of the Municipal School Professor Rita Nery, located in the neighborhood of Tenoné, which serves children from 4 to 5 years old. The survey was conducted with site visits 2 times a week for 1 month. Describes the operation of the library, such as schedule, collection, public, and activities developed with users.